A new 98 soft-switching full-bridge DC-DC converter based on secondary-side LC resonant principle for PV generation systems - Tsukiyama, D.; Fukuda, Y.; Miyake, S.; Mekhilef, Saad; Kwon, S.K.; Nakaoka, M. (2011)
This paper is mainly concerned with the state-of-the-art feasible development of a novel prototype high-efficiency phase-shift soft-switching pulse modulated full-bridge DC-DC power converter with a high-frequency power transformer, which is designed for utility-grid tied photovoltaic (PV) power inverters. The proposed high-frequency transformer (HFTR) link DC-DC converter topology is based upon a new conceptual secondary-side series resonant principle and its inherent nature. All the active power switches in the HFTR primary-side can achieve lossless capacitive snubber-based ZVS with the aid of transformer parasitic inductances. In addition to this, passive power switches in its secondary-side can also perform ZVS and ZCS transitions for input voltage and load variations. In the first place, the operation principle of the newly-proposed DC-DC converter and some remarkable features are described in this paper on the basis of the simulation analysis. In the second place, the 5 kW experimental setup of the DC-DC converter treated here is demonstrated and its experimental results are illustrated from a practical point of view. Finally, some comparative evaluations between simulation and experimental data are actually discussed and considered in this paper, together with its future works.